Amorphous silica nanoparticles trigger nitric oxide/peroxynitrite imbalance in human endothelial cells inflammatory and cytotoxicity effects. - RADOMSKI, MAREK; MEDINA MARTIN, CARLOS (My University, 2011)
BACKGROUND: The purpose of this study was to investigate the mechanism of noxious effects of amorphous silica nanoparticles on human endothelial cells. METHODS: Nanoparticle uptake was examined by transmission electron microscopy. Electrochemical nanosensors were used to measure the nitric oxide (NO) and peroxynitrite (ONOO(-)) released by a single cell upon nanoparticle stimulation. The downstream inflammatory effects were measured by an enzyme-linked immunosorbent assay, real-time quantitative polymerase chain reaction, and flow cytometry, and cytotoxicity was measured by lactate dehydrogenase assay. RESULTS: We found that the silica nanoparticles penetrated the plasma membrane and rapidly stimulated release of cytoprotective NO and, to a greater extent, production of cytotoxic ONOO(-). The low [NO]/[ONOO(-)] ratio indicated increased nitroxidative/oxidative stress and correlated closely with endothelial inflammation and necrosis. This imbalance was associated with nuclear factor ?B activation, upregulation of key inflammatory factors, and cell death. These effects were observed in a nanoparticle size-dependent and concentration-dependent manner. CONCLUSION: The [NO]/[ONOO(-)] imbalance induced by amorphous silica nanoparticles indicates a potentially deleterious effect of silica nanoparticles on vascular endothelium.
PUBLISHED
Keywords: Pharmacology; nanotoxicology; amorphous silica nanoparticles